Research advances in the therapeutic potential of xanthine oxidoreductase inhibitors for periodontitis - LI Yongshan; WU Zhicong; WANG Zixing; YU Xihuang; LIU Xi; YU Ting (口腔疾病防治, 2023)
Periodontitis is associated with abnormal purine metabolism, which is manifested by increased uric acid in host blood and increased expression of the purine-degrading enzyme, xanthine oxidoreductase (XOR), in periodontal tissues. Both XOR and uric acid are pro-oxidative and pro-inflammatory mediators under pathological conditions. Animal studies have found that injection of uric acid promotes the progression of periodontitis and that febuxostat (an XOR inhibitor) improves tissue destruction in periodontitis. Therefore, blocking the source of uric acid may be a therapeutic strategy to control the progression of periodontitis. In this article, the rationality of XOR inhibitors as potential therapeutic drugs for periodontitis is reviewed. The literature review results suggest that XOR inhibitors show antioxidative, anti-inflammatory, and anti-osteoclastic effects, and XOR inhibitors show clinical efficacy in the treatment of infectious, inflammatory and osteolytic diseases. Although there is no direct evidence to support the finding that XOR inhibitors can ameliorate periodontal microecological dysbiosis, these drugs can modulate intestinal microflora dysbiosis, and there is indirect evidence to support a beneficial effect of XOR inhibitors on periodontal microecological dysbiosis. In conclusion, XOR inhibitors may be used as immunomodulators for the adjuvant treatment of periodontitis by inhibiting inflammation, oxidative stress and anti-osteoclast effects.